Endophytes: Potential Source of Bioactive Compounds of Pharmaceutical Importance: Pharmaceutical Importance of Bioactive Compounds from Endophytes - Tahira Younis; Rahman, Lubna; Rahman, Sidra; Shinwari, Afnan Khan; Iqrar, Irum; Zabta Khan Shinwari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Microbes exist as mutualists, parasites, and symbionts or as pathogens in nature. In plant microbiota, plant immunity determines whether the interaction with microbes is friendly or hostile. Friendly interaction may have an eccentric way of mutual interrelations for a resource contribution. This interaction is called plant-endophyte mutualistic or symbiotic relation in which microorganisms (fungi, bacteria, and actinomycetes) live within robust plant tissues. It has been discovered that almost all plant species investigated by various researchers harbor one or more endophytes. They benefit their host by producing various secondary metabolites that can be employed in agriculture and medicine. Endophytes are a treasure house of many novel bioactive compounds such as steroids, tannins, terpenoids, quinones, alkaloids, saponins, and phenolic acids which makes them a potential candidate for anticancer, antibiotic, antioxidant, anti-inflammatory, antiviral, antidiabetic properties, etc. Endophytes continue to be the peculiar source of various potential drugs. This review intends to shed light on the function and potential applications of endophytes as a forthcoming source of medications for a range of illnesses/diseases as well as other potential medical uses.